OP IV – 5 Long-term air pollution and incidence of the metabolic syndrome in the population-based heinz nixdorf recall study. (18th March 2018) - Matthiessen, Clara; Lucht, Sarah; Hennig, Frauke; Ohlwein, Simone; Moebus, Susanne; Jöckel, Karl-Heinz; Hoffmann, Barbara
Abstract : Background/aim: Recently, epidemiological studies have found a link between air pollution (AP) and individual components of the metabolic syndrome (MetS), a condition predisposing to cardiometabolic diseases. However, very few studies have explored a possible association between air pollution and MetS. We analysed the effects of long-term exposure to AP on incidence of MetS. Methods: Data from the population-based prospective Heinz Nixdorf Recall study without MetS at baseline (2000–2003) were used in this study (n=3086). Mean annual exposure for size-fractioned particulate matter (PM2.5 and PM10) and nitrogen dioxide (NO2) was assessed with a land use regression model. MetS at the 5.1 year follow-up examination was defined as central obesity plus two out of four additional risk factors (i.e., elevated triglycerides, reduced high-density lipoprotein cholesterol, elevated blood pressure or elevated fasting plasma glucose). We estimated odds ratios (ORs) of MetS incidence per interquartile range (IQR), adjusting for demographic and lifestyle variables. In a two-exposure model, we investigated combined effects of air pollution and road traffic noise. Results: 299 participants developed MetS during a mean follow-up of 5.1 years. Mean air pollution exposure at baseline examination was 18.4 μg/m 3 for PM2.5, 27.7 μg/m 3 for PM10, and 30.0 μg/m 3 for NO2. All air pollutants were borderline positively associated with MetS. For example, adjusted ORs per IQR for PM10 and PM2.5 were 1.14 (0.98–1.32) and 1.19 (0.98–1.44), respectively. For NO2, the OR was lower than the PM estimates (1.03; 0.88–1.21). In the two-exposure models with both PM and noise, ORs per IQR for PM10, PM2.5, and NO2 increased slightly to 1.16 (1.00–1.35), 1.21 (0.99–1.48), and 1.06 (0.89–1.25), respectively. Conclusion: Long-term exposure to air pollution might increase the risk of developing MetS in the general population, with strongest effects seen for PM10 and PM2.5. This association remained when adjusting for long-term traffic noise exposure.